Reflections on the Evolving Triad Tutorial in a Postgraduate Art Studio. (October 2016) - Tripp, Sarah
Abstract: This article traces the evolution of the 'triad tutorial'. The triad model, predominantly used in the training of counsellors and psychotherapists, was originally combined with the art school tutorial model in the context of the Edinburgh Sculpture Workshop to enhance critical discourse between studio holders. The resulting hybrid, the 'triad tutorial', was then adapted with postgraduate students on a Master's Fine Art course at a Scottish art school. Drawing on questionnaires from a small pilot study with students, the triad tutorial is described as an evolving model that has enhanced critical discourse between students, increased student confidence and introduced students to a new reciprocal structure of critique. Links are drawn between critical self‐reflection, reciprocity and the sustainability of artistic practice. The development of the triad tutorial is described frankly, using the autobiographic timeline of the author to present the model as evolving by trial and error and born of contingency rather than design.